2009
DOI: 10.1021/ol901999f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biphenyl Proteomimetics as Estrogen Receptor-α Coactivator Binding Inhibitors

Abstract: A novel series of biphenyl proteomimetic compounds were designed as estrogen receptor-alpha (ERα) coactivator binding inhibitors. Synthesis was accomplished through a convergent approach, employing Suzuki coupling chemistry to ligate the individual modular units. Initial biological results support the ability of these compounds to compete for the ERα coactivator binding groove.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…5,12,13,[20][21][22]24,[30][31][32] SERMs and SARMs exhibit tissueselective behaviors because of the different expression levels and cohorts of coregulatory proteins found in different tissues. 7,14,32,35,37 In this article, we reconfigured the AR-TIF2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5,12,13,[20][21][22]24,[30][31][32] SERMs and SARMs exhibit tissueselective behaviors because of the different expression levels and cohorts of coregulatory proteins found in different tissues. 7,14,32,35,37 In this article, we reconfigured the AR-TIF2…”
Section: Discussionmentioning
confidence: 99%
“…26,35,36 Indeed, selective estrogen receptor modulators (SERMs) and selective androgen receptor modulators (SARMs) take advantage of the different repertoires and concentrations of coregulatory proteins in various cells to exert their tissue-selective behaviors. 7,14,32,35,37 SERMs and SARMS have convincingly demonstrated that small molecules can elicit tissue-or gene-selective effects, and recently, several groups have developed inhibitors that disrupt interactions between NRs and coactivator proteins. 7,14,31,32,35,37,38 For example, the bone-specific actions of the SARM S-101479 are the result of its failure to recruit TIF2, SRC-1, and NCoA3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Supported by theoretical data and promising results in the design of ER CBIs using biaryl scaffolds, they designed 3,3′-disubstituted bis-4,4′oxybiphenyls to mimic the hydrophobic side chains arrangement and also the electronic interactions with the charge clamp to lock the inhibitors in place (Fig 3. 4a-d) [90][91][92][93][94]. A series 3,3′-disubstituted biphenyls including 4,4′-asymmetrical phenolic-ester, amino-ester and amino-acid derivatives was prepared and their ability to disrupt ER-and AR-coactivator binding evaluated in respective cell-based transactivation assays.…”
Section: <Insert Figure 3 (Double Column)>mentioning
confidence: 99%
“…1b). 31 Direct inhibition of the receptor/co-activator protein-protein interaction, 32-37 notably using helix mimetics 35,36,38 is of potential therapeutic interest as an alternative to the use of competitive inhibitors for the ligand binding site. 39 Herein, we introduce two bifacial proteomimetic scaffolds; bis-benzamide and N-(4-aminophenyl)terephthalamidic as novel foldamers designed as tools to (a) enhance our understanding of aromatic oligoamide foldamer conformation and (b) ligands that could mimic the key side chains at i, i+3, i+4 positions of -helices that participate in PPIs mediated by such a side chain constellation.…”
Section: Introductionmentioning
confidence: 99%